1991
DOI: 10.3382/ps.0700573
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Free Fatty Acid Content and Degree of Saturation on the Apparent Metabolizable Energy Value of Fats Fed to Broilers

Abstract: To determine the influence of free fatty acid (FFA) content on the subsequent nutritive value of fats, the following were studied: tallow (FFA content of 138.4 g/kg) and tallow acid oil (FFA = 952.1 g/kg) in Experiment 1; palm oil (FFA = 57.5 g/kg) and palm acid oil (FFA = 917.5 g/kg) in Experiment 2; and soybean oil (FFA = 14.4 g/kg) and soybean acid oil (FFA = 683.4 g/kg) in Experiment 3. The two fats within each experiment were blended in proportions to give three mixtures of intermediary FFA content. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
42
2
12

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 12 publications
14
42
2
12
Order By: Relevance
“…The reduced ability of broilers to efficiently utilize glycerin co-products having relatively high free fatty acid content as indicated by their lower ME:GE ratio warrants additional discussion. Wiseman and Salvador (1991) reported a linear reduction of ME content in broiler diets containing increasing concentrations of free fatty acids, which was supported by others (Artman, 1964;Sklan, 1979) who reported that free fatty acids reduce the rate of absorption compared with lipid sources containing triglycerides and free fatty acids. This reduced absorption in products containing free fatty acids may be partially due to the absence of a monoglyceride backbone to aid absorption because the relatively low concentration of monoglycerides in the duodenum, which may depress the amount of fatty acids entering micellular solution.…”
Section: Introductionsupporting
confidence: 68%
“…The reduced ability of broilers to efficiently utilize glycerin co-products having relatively high free fatty acid content as indicated by their lower ME:GE ratio warrants additional discussion. Wiseman and Salvador (1991) reported a linear reduction of ME content in broiler diets containing increasing concentrations of free fatty acids, which was supported by others (Artman, 1964;Sklan, 1979) who reported that free fatty acids reduce the rate of absorption compared with lipid sources containing triglycerides and free fatty acids. This reduced absorption in products containing free fatty acids may be partially due to the absence of a monoglyceride backbone to aid absorption because the relatively low concentration of monoglycerides in the duodenum, which may depress the amount of fatty acids entering micellular solution.…”
Section: Introductionsupporting
confidence: 68%
“…No método tradicional com pintos, o menor CDEEA do FSOA, em relação ao da SIE e do FSO, pode ser atribuído à composição em ácidos graxos do óleo ácido de soja, que é composto, basicamente, por ácidos graxos livres. O aumento da quantidade de ácidos graxos livres em uma fonte de gordura reduz a digestibilidade e a absorção dessa gordura (Wiseman & Salvador, 1991;Vilá & Esteve-Garcia, 1996). Segundo Sklan (1979), a absorção de gordura pelas aves é precedida do rompimento (digestão) dos triglicerídeos e favorecida pela presença de monoglicerídeos resultantes desse rompimento, que ativam a secreção de bile, necessária para a formação das micelas, e a presença de ácidos graxos livres dificulta esses processos.…”
Section: * Means With Small Letters In a Row And Capital Letters In Aunclassified
“…Entretanto, a avaliação das verdadeiras contribuições energéticas das gorduras é extremamente difícil, pois envolve fatores não necessariamente associados às suas qualidades, como concentração de energia ou de gorduras e proteína na ração, idade e espécie das aves, níveis de inclusão, fontes de fibras na ração, taxa de passagem do alimento pelo sistema digestório e métodos de determinação (Rao & Clandinin, 1970;Kass et al, 1980;Mateos & Sell, 1981;Wiseman & Salvador, 1989;Wiseman & Salvador, 1991). Além desses fatores não necessariamente ligados à qualidade, o comprimento da cadeia de ácidos graxos, o grau de saturação, a quantidade de ácidos graxos livres e o conteúdo de ácido linoléico (Mateos & Sell, 1980;Nitsan et al, 1997) alteram os valores de energia metabolizável, em razão dos mecanismos de digestão e absorção das gorduras (Wiseman & Salvador, 1991).…”
Section: Introductionunclassified